Trade, transportation and environment nexus in Nigeria - Longe, Adedayo Emmanuel; Ajulo, Kayode Daniel; Omitogun, Olawunmi; Adebayo, Emmanuel Olajide (The European Journal of Applied Economics, 2018)
This study investigates trade, transportation and environment nexusin Nigeria. The main objective of the study is to incorporate transportationactivities and trade into the EKC model seeing transportationas an important factor that determines environmental degradation inNigeria. Annual data from 1984 to 2014 is used in the study, whereasARDL estimation technique was adopted to analyse the data. The resultsshow that all the variables have a positive significant correlationwith carbon emissions in Nigeria except trade that was negative andinsignificant. According to ARDL estimates,trade, import transportservices and GDP per capita have positive impact on CO2 emissions inthe long-run while in the short-run, the result shows that trade, GDPper capita, energy consumption and transport services are capable ofcorrecting about 74% deviation of carbon emissions back to long-runequilibrium. Based on the findings, drawn conclusion stipulates thatenergy consumption and trade are the main determinant factors thatcontribute to carbon emission and appropriate attention should begiven to energy consumption by considering alternative efficient energysources to curb the increasing emission in Nigeria.